Health literacy and prevention practices for COVID-19: a cross-sectional study in Brazilian adults (Research, Society and Development, 2021)
Objective: Was to assess the health literacy of the population in the city of Jundiai in relation to the adoption of practical measures to prevent the disease COVID-19. Methodology: Cross-sectional study with 290 adults of epidemiological survey about COVID-19, being 150 with negative tests and 140 with positive tests. Through phone calls, it was applied the Health Literacy Scale (HLS-14), between October 2020 and April 2021. The Chi-Square test (p